STRAIN AND LOCAL HETEROGENEITY IN THE FORSTERITE-FAYALITE SOLID SOLUTION - Tarantino S.C.; Carpenter M.A.; Domeneghetti M.C. (My University, 2003)
Infrared powder-absorption spectra of nine natural and five synthetic olivine samples across the forsterite-fayalite join have been investigated at room temperature in the range 70-1400 cm-1. Variations of peak positions as a function of Fe content are close to linear for those vibrational bands whose trend could be followed across the solid solution. Line-broadening has been quantified by autocorrelation analysis. Positive deviations from linearity of the line-broadening parameter, Δcorr, for groups of bands at low energies are consistent with the existence of local elastic strain heterogeneities at intermediate compositions in the solid solution. It also appears that the structure of forsterite is more homogeneous than Fe-rich olivines in relation to local elastic strain effects. Positive deviations from linearity of the line-broadening parameter for the low-energy regions scale linearly with calorimetric data for the enthalpy of mixing. This close correlation between line-broadening in IR spectra and calorimetric enthalpies of mixing has now been observed for four different binary solid solutions, and there is a further, qualitative correlation with bulk modulus.
Keywords: OLIVINE; SOLID SOLUTION; IR SPECTROSCOPY; LINE-BROADENING; ELASTIC STRAIN